EFFECT OF DIFFERENT LEVELS OF NDF ON VOLUNTARY FEED INTAKE, DRY MATTER DIGESTIBILITY AND NUTRIENTS UTILIZATION IN DRY NILI RAVI BUFFALOES - S. Ahmad; M. A. Jabbar; A. Khalique; Saima; F. Shahzad; N. Ahmad; M. Fiaz; U. Younas (Journal of Animal and Plant Sciences, 2014)
A study was conducted to determine voluntary nutrient intake, its digestibility and optimum fiber requirements in dry Nili Ravi buffaloes kept at Buffalo Research Institute (BRI), Pattoki district Kasur Punjab province Pakistan for a period of 60 days. The buffaloes (n=25) were selected from amongst the existing herd and randomly divided into five groups. These animals were fed isonitrogenous and isocaloric diets i.e. A, B, C, D and E based on different NDF levels i.e.23, 28, 33, 38 and 43%, respectively. Nutrient intake and nutrients digestibility differed (P<0.001) significantly among the dietary groups. In group C dry matter, (14.42±0.09 kg/d), crude protein (1.58±0.01 kg/d) and in group E neutral detergent fiber intake (5.52±0.010kg/d) were highest than rest of other treatment groups. Whereas, DM, and NDF digestibility was observed highest in the group B (62.5±1.04kg/d) and C (64.46±0.99kg/d) respectively as compared to other groups. The CP digestibility was non-significantly different among treatment groups. The average weight gain in dry Nili Ravi buffaloes was 0.48±0.045 kg/d. The results of this study indicate that dietary NDF level (33.0%) is better in terms of nutrients intake and digestibility in these animals.
Keywords: NDF; Nili Ravi buffalo; dry matter; digestibility; weight gain